Effect of Build Parameters on the Mechanical Behavior of Polymeric Materials Produced by Multijet Fusion. Issue 9 (19th September 2022) - Chen, Andrew Y.; Chen, Ailin; Wright, Jake; Fitzhugh, Andrew; Hartman, Aja; Zeng, Jun; Gu, Grace X.
Abstract : The figure depicts the multi‐jet fusion printing of specimens used to study the effect of changing build parameters on mechanical properties. At each layer, heat is applied to a surface with fusing agent (black) deposited atop fresh powder. A transparent build volume shows the temperature distribution (white‐red color map) on the printed layer. Further details can be found in the article number 2100974 by Grace X. Gu and co‐workers. For the image, we would like to credit: "Fabiola Leyva from HP Labs".